Pemberdayaan Kader Kesehatan sebagai Social Support bagi Pasien Stroke - Loetfia Dwi Rahariyani; Kusmini Suprihatin; Yessy Desy Arna; M. Afif Hilmi Masyfahani (Universitas Muhammadiyah Yogyakarta, 2022)
The majority of stroke clients experience sequelae that can cause stress in the home care process, both for stroke patients and their families as caregivers. As a result, social support involving cadres for families with stroke patients is necessary. The service activity aims to increase the knowledge of health cadres about social support for stroke patients and implement social support for stroke patients and their families. The implementation method was through two stages. The first stage was the training of health cadres in Gedangan District with 70 cadres from 15 villages, while stage 2 was empowering health cadres in the community. Each cadre provides social support for families/stroke patients according to where the cadres live. Each cadre was provided with a questionnaire, and the data were analyzed descriptively. The activity results stated that all cadres found that stroke patients and their families experienced stress due to the illness, agreed that stroke patients and their families needed attention, and citizens needed to be prepared if someone had a stroke. In addition, the knowledge of health cadres increases, and cadres are happy with the social support program for stroke patients and their families. The visited stroke patients were happy because they received attention and support. In the long run, this program can be continued in every village by empowering health cadres as agents of reform in the health sector.